Combined apophyseal and epiphyseal fixation of Ogden type IIIA/IV tibial tubercle avulsion fractures provides favorable stability compared to isolated apophyseal screw fixation - a biomechanical study. - Peez, Christian; Zderic, Ivan; Richards, R. Geoff; Drenchev, Ludmil; Skulev, Hristo K.; Gueorguiev, Boyko; Kittl, Christoph; Raschke, Michael J.; Herbst, Elmar (European Journal of Trauma & Emergency Surgery, 2025)
Purpose: Current literature lacks recommendations regarding proper fixation of tibial tubercle avulsion fractures involving the proximal tibial epiphysis (Ogden fractures). Therefore, the aim of this study was to compare isolated apophyseal screw fixation and additional fixation techniques in Ogden fractures. Methods: Two different types of apoepiphyseal tibial tubercle avulsion fractures were created in 40 proximal tibiae according to the modified Ogden classification: (1) Ogden type IIIA and (2) Ogden type IV. The fractures were fixed with either isolated apophyseal screws or additionally with a medial plate or epiphyseal screws. All specimens were biomechanically tested under progressively increasing cyclic loading until failure, while capturing the interfragmentary movements with motion tracking. Results: Augmentation of apophyseal screw osteosynthesis by a medial plate in Ogden IV fractures or epiphyseal screws in Ogden IIIA fractures exhibited significantly higher cycles to failure and failure loads (P< 0.05), and significantly less axial displacement (P < 0.05) compared to isolated apophyseal screw fixation. Fixation of Ogden type IIIA fractures resulted in significantly less axial displacements and higher construct stiffness, cycles to failure and failure loads compared to Ogden type IV fracture (P < 0.001). Fracture gap opening did not differ significantly between the fixation techniques. Conclusions: Augmented apophyseal screw fixation of apoepiphyseal tibial tubercle avulsion fractures provides greater biomechanical stability than isolated apophyseal screw fixation. Regardless of fixation technique, Ogden type IV fractures are more unstable than Ogden type IIIA fractures, so an individualized treatment strategy based on fracture morphology is crucial. In case of an Ogden type IIIA or Ogden type IV fracture, surgeons should consider adding epiphyseal screws or a medial plate osteosynthesis to apophyseal screw fixation to best neutralize forces of the extensor mechanism, as long as the often compromised soft tissue envelope can tolerate greater surgical invasiveness.